2015
DOI: 10.3389/fnhum.2015.00020
|View full text |Cite
|
Sign up to set email alerts
|

Altered retrieval of melodic information in congenital amusia: insights from dynamic causal modeling of MEG data

Abstract: Congenital amusia is a neuro-developmental disorder that primarily manifests as a difficulty in the perception and memory of pitch-based materials, including music. Recent findings have shown that the amusic brain exhibits altered functioning of a fronto-temporal network during pitch perception and short-term memory. Within this network, during the encoding of melodies, a decreased right backward frontal-to-temporal connectivity was reported in amusia, along with an abnormal connectivity within and between aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 91 publications
(160 reference statements)
13
58
0
Order By: Relevance
“…Amusia may be congenital (i.e., developed at birth or in early childhood) or can be acquired through brain injury to areas important for music perception (e.g., bilateral damage to superior temporal lobes) (Peretz, 2001; Peretz et al, 1994). Music perception deficits in amusia appear to be linked to an underlying impairment in fine-grained pitch perception (e.g., Foxton et al, 2004; Peretz et al, 2002; Vuvan et al, 2015), either due to deficits in pitch processing (e.g., Cousineau et al, 2015) or deficits in pitch memory (Albouy et al, 2015, 2013a; Gosselin et al, 2009; Tillmann et al, 2016, 2009; Williamson et al, 2010; Williamson and Stewart, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Amusia may be congenital (i.e., developed at birth or in early childhood) or can be acquired through brain injury to areas important for music perception (e.g., bilateral damage to superior temporal lobes) (Peretz, 2001; Peretz et al, 1994). Music perception deficits in amusia appear to be linked to an underlying impairment in fine-grained pitch perception (e.g., Foxton et al, 2004; Peretz et al, 2002; Vuvan et al, 2015), either due to deficits in pitch processing (e.g., Cousineau et al, 2015) or deficits in pitch memory (Albouy et al, 2015, 2013a; Gosselin et al, 2009; Tillmann et al, 2016, 2009; Williamson et al, 2010; Williamson and Stewart, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the pitch-related deficits may be caused by dysfunctions in the frontal cortex (Hyde et al, 2006(Hyde et al, , 2011Albouy et al, 2013). For example, Albouy et al (2013) revealed that low gamma oscillations (30 -40 Hz range) in the right dorsolateral prefrontal cortex (DLPFC) were lower in amusics than in healthy controls. A third possibility, however, is that individuals with congenital amusia have abnormal pitch responsive region(s) in their auditory cortex, despite the fact that the auditory cortex seems to have normal responses to pitch changes (Hyde et al, 2011;Moreauet al, 2013; but see Albouy et al, 2013;Zendel et al, 2015).…”
Section: Review Of Norman-haignere Et Almentioning
confidence: 99%
“…For example, Albouy et al (2013) revealed that low gamma oscillations (30 -40 Hz range) in the right dorsolateral prefrontal cortex (DLPFC) were lower in amusics than in healthy controls. A third possibility, however, is that individuals with congenital amusia have abnormal pitch responsive region(s) in their auditory cortex, despite the fact that the auditory cortex seems to have normal responses to pitch changes (Hyde et al, 2011;Moreauet al, 2013; but see Albouy et al, 2013;Zendel et al, 2015). NormanHaignere et al (2016) examined the third possibility by investigating pitch-specific activation in the auditory cortex.…”
Section: Review Of Norman-haignere Et Almentioning
confidence: 99%
See 2 more Smart Citations